Epigenetic Deregulation of the Histone Methyltransferase KMT5B Contributes to Malignant Transformation in Glioblastoma - López, Virginia; Tejedor, Juan Ramón; Carella, Antonella; García, María G.; Santamarina-Ojeda, Pablo; Pérez, Raúl F.; Mangas, Cristina; Urdinguio, Rocío G.; Aranburu, Aitziber; de la Nava, Daniel; Corte-Torres, María D.; Astudillo, Aurora; et al. (Frontiers in Cell and Developmental Biology, 2021)
Glioblastoma multiforme (GBM) is the most common and aggressive type of brain tumor in adulthood. Epigenetic mechanisms are known to play a key role in GBM although the involvement of histone methyltransferase KMT5B and its mark H4K20me2 has remained largely unexplored. The present study shows that DNA hypermethylation and loss of DNA hydroxymethylation is associated with KMT5B downregulation and genome-wide reduction of H4K20me2 levels in a set of human GBM samples and cell lines as compared with non-tumoral specimens. Ectopic overexpression of KMT5B induced tumor suppressor-like features in vitro and in a mouse tumor xenograft model, as well as changes in the expression of several glioblastoma-related genes. H4K20me2 enrichment was found immediately upstream of the promoter regions of a subset of deregulated genes, thus suggesting a possible role for KMT5B in GBM through the epigenetic modulation of key target cancer genes.